(untitled) (ASA, 2021)
To realize the goal of marriage, the prospective husband and prospective wife before making a choice to build a household, it is necessary to have equality and a common vision and mission, at least to have equality in terms of religion, belief, social status, and so on. The equality and equality between husband and wife in the scope and context of marriage is called kafaah. Kafaah in marriage is very important because Kafaah is the foundation and main support for achieving the goal of marriage, namely the establishment of a sakinah, mawaddah, warahmah family. Kafaah is not a requirement for a valid marriage, but Kafaah has an important role in the formation of a harmonious family. Kafaah in marriage is the balance and harmony between the prospective wife and the prospective husband so that each candidate does not find it difficult to get married. Or a man is equal to his future wife, equal to position, equal in social level and equal in character and wealth. Therefore, it is recommended that both prospective husbands and prospective wives get to know each other and know each other’s personalities, including their religious similarities, social status similarities, and living conditions.